The meaning of the ritual concept of aliran kebatinan perjalanan (akp) in the Karang Pawitan community, Pakutandang Village, Ciparay District, Bandung Regency - Irham Yuflih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
This paper examines the meaning of the ritual concept of Aliran Kebatinan Kepercayaan in the Karangpawitan community, Bandung Regency. The center of human ritual activity is God, so humans have a creative attitude in “searching” for God, which is reflected in the original culture. This research aims to discover the concept of God in Aliran Kebatinan Kepercayaan in the Karangpawitan community. The method used qualitative research using Mircea Eliade's phenomenological and historical approach. The results show that the concept of God in Aliran Kebatinan Kepercayaan is that God is everywhere, in the hearts of every human. However, God does not have a form and color. The human cannot compare God with anything in this universe. The concept of awang-awang, uwung-uwung means that Almighty God has already existed when heaven and earth do not yet exist. The Aliran Kebatinan Kepercayaan has no specificity in rituals or the process of worship. The contribution of this study is to determine that the applied ritual is to have a clear mind because people must pass some stages before finally merging with God or being united with God. It is essential to know that the offerings have meaning and good knowledge in the lives and livelihoods of the devotees.